Feasibility of nanofiltration process for high efficient recovery and concentrations of food waste-derived volatile fatty acids. (August 2022) - Pervez, Md. Nahid; Mahboubi, Amir; Uwineza, Clarisse; Sapmaz, Tugba; Zarra, Tiziano; Belgiorno, Vincenzo; Naddeo, Vincenzo; Taherzadeh, Mohammad J.
Abstract: Various methods exist for the recovery of volatile fatty acids from organic mixed waste effluents, and among them, the membrane filtration process holds a great promise over other recovery methods due to their simplicity, sustainability and high efficiency. Hence, in this study, nanofiltration experiments were carried out using two commercial nanofiltration membranes of 200–300 Da and 300–500 Da under various pH (4, 5.4, 7 and 9) at constant pressure (15 bar) and temperature of 20-21 °C in order to achieve a higher amount of volatile fatty acids from the real mixed food waste-based effluent. Results showed that solution pH plays an important role in the physicochemical parameters such as total solids removal rate was above 80 % at pH 4, chemical oxygen demand, ammonia and phosphorus removed to some extent at pH 9. Subsequently, the concentration and recovery percentages of volatile fatty acids increased with solution pH 9; in particular, lower molecular weight cut-off membrane, i.e., 200–100 Da, appeared to be more effective with an increased concentration of total volatile fatty acids (16.94 g L −1 ) and recovery percentage above 90 % at pH 9. Membrane performance was also evaluated and correlated with recovery performance in terms of permeate flux reduction at lower pH. An important finding of this study was the concentration and recovery percentages of volatile fatty acids reached around 96 % after 3rd cycle by conducting a repeated sequencing nanofiltration process, which was identified as a promising option to enhance the recovery percentages of volatile fatty acids. Graphical abstract: Unlabelled Image Highlights: Food waste represents a sustainable source for volatile fatty acids production. The 200–100 Da nanofiltration membrane showed better volatile fatty acid recovery. VFAs recovery percentage of 90 % was achieved at higher pH (pH 9). Alongside, the highest flux occurred at pH 4 (for XN at 84.79 l m −2 h −1 ). Sequencing nanofiltration is a promising option to improve recovery percentages.